The verb in the Spanish of Amazonian indigenous school migrants - Falcón Ccenta, Pedro M. (2002)
The present work constitutes a case study regarding the written production of Spanish by indigenous Amazonian schoolchildren in schools in Lima. We try to characterize the difficulties in the written use of VF, pointing out the particularities that verbal constructions present.Likewise, we evaluate the socioeconomic and cultural aspects that contextualize the linguistic behavior of indigenous Amazonian schoolchildren, as well as the implications that these generate in the development of the educational process.The description of the use of verbs in the aforementioned sociocultural framework. allows us to observe that the indigenous schoolboy not only faces interference from his native language in Spanish, but also from dialectal Spanish (Amazonian) in standard Spanish (written).